2011
DOI: 10.1039/c1cy00136a
|View full text |Cite
|
Sign up to set email alerts
|

Support effects on the structure and performance of ruthenium catalysts for the Fischer–Tropsch synthesis

Abstract: The influence of support and metal precursor on Ru-based catalysts has been studied in the\ud Fischer–Tropsch synthesis (FTS) combining flow reactor and quasi in situ infrared spectroscopy\ud experiments. A series of supported ruthenium catalysts (3 wt.%) have been prepared using two\ud different TiO2 (P25, 20% rutile and 80% anatase; Hombifine, 100% anatase) and SiO2Al2O3\ud (28% Al2O3) as supports and RuCl3nH2O as metal precursor. The catalysts were labeled as\ud RuTi0.8, RuTi1 and RuSA respectively. Another… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 73 publications
0
15
0
Order By: Relevance
“…Generally, titania is known to be a more reducible support than zirconia [4]. According to previous works, the existence of a weak interaction of RuO x with TiO 2 was correlated to the presence of a titania anatase phase of support, as this was notably evidenced by TPR studies where low temperature effects were principal [31].…”
Section: Discussionmentioning
confidence: 93%
“…Generally, titania is known to be a more reducible support than zirconia [4]. According to previous works, the existence of a weak interaction of RuO x with TiO 2 was correlated to the presence of a titania anatase phase of support, as this was notably evidenced by TPR studies where low temperature effects were principal [31].…”
Section: Discussionmentioning
confidence: 93%
“…The Fischer-Tropsch synthesis (FTS) enables a switch from coal, natural gas and biomass to ultra-clean transportation fuels and valuable chemicals, in which syngas is catalytically converted into hydrocarbons by means of the hydrogenation of adsorbed CO on transition metals. [1][2][3][4][5] The corresponding catalytic activity is considered to depend on the number of available surface metal sites. 3,6,7 In order to achieve high surface active sites, some refined approaches have been explored to prepare metal nanoparticles with high surface/interior atom ratio on the high-surface-area oxide supports, such as SiO 2 , Al 2 O 3 , TiO 2 and ZnO being the most frequently used.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, nanostructured systems including those based on metal ruthenium were actively studied for their higher reaction rate and selectivity for the main products [6][7][8][9][10]. Commonly used supports for FT catalysts are silica, alumina, zirconia, and titanium oxide [5,11,12]. Alumina-supported catalysts could give higher ruthenium dispersion compared to a silica carrier, while SiO 2 -based catalysts are characterized by low acidity resulting in higher long-chain hydrocarbon selectivity [13].…”
Section: Introductionmentioning
confidence: 99%
“…Alumina-supported catalysts could give higher ruthenium dispersion compared to a silica carrier, while SiO 2 -based catalysts are characterized by low acidity resulting in higher long-chain hydrocarbon selectivity [13]. For carbon nanotubes as a carrier in the Fischer-Tropsch synthesis, it was shown that placing metal particles inside the nanotubes leads to an increase in the efficiency of the catalysis [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%